El impacto de Facebook en jóvenes de La Calera del cantón Cotacachi, en la elección de un candidato a la presidencia periodo mayo - octubre 2023 - Narváez Pozo, Luis Danilo (2024)
This research was conducted in the La Calera community, located just a few minutes from the urban center of Cotacachi, in the province of Imbabura. The aim was to analyze the impact generated by the social network, known as Facebook, on young people between 16 and 17 years old in this rural area. This study is framed within the context of the electoral campaign for the anticipated 2023 presidential elections, taking into account the optional voting rights of adolescents. To achieve this, the goal was to determine the interaction that adolescents have with this digital platform. Additionally, it aimed to verify the exercise of the optional voting rights of the studied group to establish strategies for actively involving young people in the decision-making processes of their community, municipality, province, and country. Within the theoretical framework, various concepts regarding Political Communication were established, emphasizing their significance in the development of this research. Similarly, statistics related to the use of social networks in Ecuador were analyzed, with a specific focus on the rural sectors of the Cotacachi canton. On the other hand, the importance of optional voting was considered and how it has been promoted since the beginning of its legal validity. The research results made it possible to visualize the participation of young people in the political events; however, the social network does influence the exercise of their voting right. In conclusion, Facebook has a media impact on the decision-making of adolescents between 16 and 17 years old in the La Calera community.